2010
DOI: 10.1093/fampra/cmq044
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associations of partner abuse in women attending Russian general practice

Abstract: the high prevalence of partner abuse is consistent with international findings in general practice-based studies. The predominantly negative attitude of women towards being asked about abuse is a challenge to future domestic violence interventions in Russian practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 17 publications
3
29
0
Order By: Relevance
“…The scale has been translated into eight languages and reliability and validity have been demonstrated in various contexts and populations 822 26–28…”
Section: Introductionmentioning
confidence: 99%
“…The scale has been translated into eight languages and reliability and validity have been demonstrated in various contexts and populations 822 26–28…”
Section: Introductionmentioning
confidence: 99%
“…Findings from the National Violence Against Women Survey revealed that 25% of U.S. women and 8% of U.S. men reported a history of being raped and/or physically assaulted by a spouse or partner at some time in their lives [2]. In Russia, results from the limited studies conducted among several different samples all demonstrate a high lifetime prevalence (from 23% perpetration and 26% victimization among STI patients to 46% perpetration among HIV-infected substance-using men), which calls for more research to examine factors related to IPV in this country [3], [4], [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…More than one-third of women in Russia have been victims of male partner-perpetrated intimate partner violence (IPV) (Horne, 1999; Kalichman et al, 2000; Lokhmatkina et al, 2010), and victims of IPV are at increased risk for contracting HIV (World Health Organization [WHO], 2005). Mechanisms for the association between IPV and HIV include both greater sexual risk taking (e.g., sex trade involvement, non-use of condoms) and substance use (e.g., injection drug use, risky sex while intoxicated) among victims of IPV, according to findings from Russia (Kalichman et al, 2000; Zhan et al, 2012), Ukraine (Dude, 2007), South Africa (Jewkes et al, 2006) and the United States (US) (Bogart et al, 2005; Dude, 2007; El-Bassel et al, 2001, 2005a; Panchanadeswaran et al, 2010; Schmuel & Schenker, 1998; Silverman et al, 2011; Silverman et al, 2001).…”
Section: Introductionmentioning
confidence: 99%